The Extended Self : Architecture, Memes and Minds. - Abel, Chris (Manchester University Press, 2016)
In this wide-ranging study of architecture and cultural evolution, the author argues that underlying the global environmental crisis is a general resistance to changing personal and social identities shaped by a technology-based culture and its energy-hungry products. The book traces the roots of that culture to the coevolution of Homo sapiens and technology, from the first use of tools as artificial extensions of the human body, to the motorised cities spreading around the world, whose uncontrolled effects are changing the planet itself. Advancing a new concept of the meme, called the 'techni.